1997
DOI: 10.1074/jbc.272.50.31301
|View full text |Cite
|
Sign up to set email alerts
|

A Novel White Laccase from Pleurotus ostreatus

Abstract: Two laccase isoenzymes (POXA1 and POXA2) produced by Pleurotus ostreatus were purified and fully characterized. POXA1 and POXA2 are monomeric glycoproteins with 3 and 9% carbohydrate content, molecular masses of about 61 and 67 kDa by sodium dodecyl sulfate polyacrylamide gel electrophoresis, of about 54 and 59 kDa by gel filtration in native conditions, and of 61 kDa by matrix-assisted laser desorption ionization mass spectrometry (only for POXA1) and pI values of 6.7 and 4.0, respectively. The N terminus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
218
1
14

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(250 citation statements)
references
References 24 publications
17
218
1
14
Order By: Relevance
“…Absorption spectrum of Lac 1 As shown in Fig. 2, the absorption spectrum of Lac 1 had typical characteristics of copper containing enzymes, 38,39) having an absorption peak at 610 nm and a shoulder at around 350 nm. This indicates that Lac 1 contains a type-1 copper atom, which is responsible for the blue color of the concentrated enzyme (shown by the absorption peak at 610 nm) and type-3 binuclear copper atoms (shown by the absorption shoulder at 350 nm).…”
Section: Molecular Mass and Pi Of Lacmentioning
confidence: 93%
“…Absorption spectrum of Lac 1 As shown in Fig. 2, the absorption spectrum of Lac 1 had typical characteristics of copper containing enzymes, 38,39) having an absorption peak at 610 nm and a shoulder at around 350 nm. This indicates that Lac 1 contains a type-1 copper atom, which is responsible for the blue color of the concentrated enzyme (shown by the absorption peak at 610 nm) and type-3 binuclear copper atoms (shown by the absorption shoulder at 350 nm).…”
Section: Molecular Mass and Pi Of Lacmentioning
confidence: 93%
“…One unit of LiP activity was defined as the amount of enzymes catalyzing the formation of 1µmol of veratraldehyde per minute under the assay conditions. Laccase activity was determined by monitoring the oxidation of 2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) at 420nm following the method of Palmieri et al [26]. The reaction mixtures (1 ml) were prepared using 20 µl of culture broth, 880 µl of citratephosphate buffer (pH 3.0) and 100 µl 1 mM ABTS, and the temperature was adjusted to 30°C.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…No beads were formed for MgSO 4 and HgCl 2 , when used as cross-linkers either alone or in combination with CuSO 4 . Laccase is a copper-dependent enzyme, and thus, Cu ions play an important role in maintaining the catalytic mechanism of laccase (Palmieri et al 1997;Duran et al 2002). It was earlier reported that Cu-alginate laccase from Trametes villosa gave better immobilization yield than Ca-alginate for laccase (Brandi et al 2006).…”
Section: Resultsmentioning
confidence: 99%